Adoption of Lean Construction and AI/IoT Technologies in Iran's Public Construction Sector: A Mixed-Methods Approach Using Fuzzy Logic - UĞURAL, MEHMET NURETTİN; AGHILI, SEYEDARASH; Burgan, Halil Ibrahim (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The construction sector in Iran faces substantial inefficiencies, including high material wastage, posing environmental and economic risks. This study investigated the adoption of Lean Construction (LC) practices and AI/IoT technologies in Iran's public construction sector using a mixed-methods approach. This research examined the organizational, technical, and infrastructural factors across four key provinces-Tehran, Isfahan, Khorasan Razavi, and Fars-and employed fuzzy logic to address the uncertainties in adoption decisions. Data from 28 key stakeholder interviews were analyzed using Python 3.9, with libraries such as Pandas 1.3.3, NumPy 1.21.2, and skfuzzy 0.4.2 for the statistical analysis and NVivo 12 for the thematic coding. The analysis revealed that organizational readiness and leadership support were the critical drivers of adoption, particularly in Isfahan and Khorasan Razavi, which exhibited the highest adoption likelihood scores (0.5000). Tehran and Fars showed slightly lower scores due to regulatory barriers and financial limitations. The findings highlight the need for targeted leadership training, regulatory reforms, and infrastructure investments to accelerate the adoption of these technologies. This study aligned with the Sustainable Development Goals (SDG 9: Industry, Innovation, and Infrastructure and SDG 11: Sustainable Cities and Communities) by offering practical recommendations for advancing sustainable practices in Iran's construction sector. The insights provided have broader implications for other developing economies facing similar challenges, contributing to global efforts toward sustainable development.
Keywords: AI/Iot Adoption; Fuzzy Logic; Lean Construction; Public Construction; Sustainable Development Goals (SDGs; Technology Adoption in Construction